Customizing thermally-reduced graphene oxides for electrically conductive or mechanical reinforced epoxy nanocomposites. (August 2017) - Vazquez-Moreno, J.M.; Yuste-Sanchez, V.; Sanchez-Hidalgo, R.; Verdejo, R.; Lopez-Manchado, M.A.; Fernández-García, L.; Blanco, C.; Menéndez, R.
Graphical abstract: Highlights: Custom-made graphene-based polymer nanocomposites. Effect of thermally reduced graphene oxides synthesis on epoxy nanocomposites. The dispersion is heavily influenced by the specific surface area and remaining oxygen groups on the graphene. Electrical conductivity is directly dependent on the reduction temperature. Mechanical reinforcing is inversely dependent on the reduction temperature. Abstract: Graphene oxide (GO) can be produced through diverse synthetic routes in large quantities that lead to clear differences in the resulting graphene morphology and properties. Here, we analysed the effect of several thermally reduced graphene oxides (TRGOs), at two different concentrations, on the electrical and mechanical properties of epoxy resin nanocomposites. Natural graphite was oxidised using two methods, Brodie (GO-B) and Hummers (GO-H), and, then, thermally reduced at different temperatures, 700, 1000, and 2000 °C. Intrinsic graphene properties, such as remaining oxygen groups, specific surface area, and aspect ratio, among others, have a profound effect on the final properties of the nanocomposite. The dispersion state was heavily influenced by the specific surface area and the remaining oxygen groups on the graphene. Meanwhile, the electrical and mechanical properties showed a strong and opposite dependency with the reduction temperature, with low temperatures resulting in flakes with high reinforcing characteristics and high temperatures in flakes with high electrical conductivity performance. Finally, TRGOs synthesised via Hummers and reduced at low temperatures appeared to be more suited as reinforcing particles, while TRGOs synthesised via Brodie were more effective as electrically conductive nanofillers.